Persepsi User Terhadap Sistem Klaim Bpjs Kesehatan Dalam Kerangka Technology Acceptance Model (TAM) Pada Rumah Sakit - Evita Yulianti; Nur Fitriyah; Adhitya Bayu Suryantara (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
This study aims to determine user perceptions of the BPJS health claim submission system that has been applied to the Mataram City Regional General Hospital. The research method used is descriptive with a qualitative approach. Data collection techniques through interviews and documentation. The informants in this study are IKJK, Claims Staff, Internal Verifier, Admin Center, Admissions Accountant, Outpatient Administration Staff, and Inpatient Administration Staff at the Mataram City Hospital. The results of this study can be said that the application of a BPJS submission system at the Mataram City Hospital which has been analyzed using the TAM model has been running quite effectively, where the INA-CBG E-Claim application has started the work process and performance of the Mataram City Hospital staff. In addition, the ease of use is quite good where the menus and features in the application are easy to reach. This INA-CBG's E-Claim application for officers claims that it really provides convenience in helping the process of submitting claims to the office. So that the submission time is always claimed on time. Although the INA-CBG E-Claim application in the convenience of officers is still claimed, this E-Claim application also has several weaknesses, namely there are errors in the application caused by the maintenance process from the head office. In addition, the process of paying claims submitted takes 14 working days from the claim submitted by the hospital. Keywords: Percepcien, Hospital, claim submission system, TAM, User